VILLAGE FUNDS LOCAL ACCOUNTABILITY PROBLEM : (Study of Village Government Together with the Village Consultative Body (BPD) Accountability in Village Funds Development in Masalembu District) - Haniah Hanafie; Masrul Huda (Iapa Proceedings Conference, 2018)
This paper aims to describe village funds local accountability problem at local level (Masalembu District). Observations and interviews are used as data collection techniques. The research found that village government together with the Village Consultative Body (BPD) accountability on village funds development was weak, becouse there is no cooperative between Village Consultative Body (BPD) with village government. In conclusion that Village Consultative Body (BPD) needs to be involved in village development evaluating and planning.